ELEMEN-ELEMEN HUKUM ISLAM DALAM UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Harahap, Ikhwanuddin (IAIN Padangsidimpuan, 2014)
Abstract: Islam is comprehensive religion that regulates all of the human life aspects. It concerns about politic, law, social, economic, and also family life. In Islamic perspective, family is the safety home for all member of the family. Â But in fact, the family can be â the hellâ for the member of the family; such as husbands, wives or childen. Facts show that most of the violence is done by husbands to wives. Â In Indonesia, the victims of the violence in family life do not exposs the violence. The cases of violences in family life make the government regulate Undang-Undang No. 23 Tahun 2004 about the Â Penghapusan Kekerasan Dalam Rumah Tangga (KDRT). It restrics all kinds of violences in family, namely physical violence such as beating, slaping, kick, biting, marital rape, etc., and non- physical violence such as intimidation, threat, terror, etc. This article tries to describe the IslamicÂ law angels on Undang-Undang No. 23 Tahun 2004 about theÂ Penghapusan Kekerasan Dalam Rumah Tangga (KDRT).Keywords: Islamic law, violence, domesticÂ Abstrak: Islam adalah agama yang komprehensif yang mengatur semua aspek kehidupan manusia. Ini menyangkut tentang politik, hukum, sosial, ekonomi, dan juga kehidupan keluarga. Dalam perspektif Islam, keluarga adalah rumah aman untuk semua anggota keluarga. Namun pada kenyataannya, keluarga dapat menjadi